Proposta e avaliação de um método com alternância de cabos para a instalação de equipamentos submarinos - Araújo Neto, Elói Daniel de (2017)
The development of oil and gas subsea exploration and production systems for ultra-deep-water requires heavy and complex subsea equipment. Usual installation methods for these structures are often limited by resonance effects for commonly used cables. A novel operational procedure based on the composition of steel wire and polyester ropes is proposed by this work in order to mitigate those effects. Numerical simulations were performed using SITUA-Prosim program to check adopted premises in the proposal of the novel subsea equipment installation method. Results show that the premises are met, which enables new studies to develop this method and/or its variations.